Układ władzy w polskich rodzinach wiejskich w latach siedemdziesiątych - Nowak, Waldemar (Wydawnictwo Naukowe UAM, 2003)
The paper deals with the problem of power in peasants’ families. Attention was paid to the evolution of the dictatorial type of the family and to a new distribution of power.
Power system in peasants’ families